KONSEP RUDRA DALAM VEDA - Surada, I Made (PANGKAJA, 2012)
AbstractHinduism is one of big Religion in world. Holy book of Hinduism is Veda. From Veda Hinduism teaching emit a stream of. In God Veda is called Agni or Indra or Waruna, in Upanisad God is called Brahman, and there is also Rudra. Rudra represent atmosferis deity which minor relative in Rgveda, even that way he/she draw physically, with only there are three rhyme (gita) concerning it and totalize about twenty seven reference modestly.But along this minor deity time journey have rounded into glorious and strong Rudra-Siva deity, that is third Deity from Trilogy Hindu, as result of merger with a few the nature of god like all non-Arya nation deity. Conception Siwa woke up do not only from confidence of Veda and tradisisemata, but because us have owned elementary form from Siwa pasupatiurdhvalinga yogisvara trimukha in civilization of Harappa before Veda. However, we here growth seharusnyamemeriksa conception Rudra step by step as found in Kesusastraan Veda. By shares early kesusastraan of our Veda interpret Samhitas, Brahmanas, Aranyakas And Upanisads, is successively degraded by under Supertitous formula, Vidhi, Arthavada and Vedanta. Last Phase from kesusasatraan of Veda shown by Sutras which shortly and systematic relate to Veda ritual in one side, and with customary law on the other side him.